Introducing a reserve waiting list initiative for elective general surgery at a District General Hospital. Issue 3 (19th August 2019) - Antoniou, Vaki; Burke, Olivia; Fernandes, Roland
Abstract : Cancelled operations represent a significant burden on the National Health Service in terms of theatre efficiency, financial implications and lost training opportunities. Moreover, they carry considerable physical and psychological effects to patients and their relatives. Evidence has shown that up to 93% of cancelled operations are due to patient-related factors. An analysis at our District General Hospital revealed that approximately 18 operations are cancelled on the day of surgery each month. This equates to 27 hours of allocated operating time valued by the trust as £67 500, not being used effectively. This retrospective quality improvement report aims to reduce unused theatre time due to cancelled elective operations in general surgery theatres—thereby improving theatre efficiency and patient care. To ascertain the baseline number of cancelled operations, an initial review of theatre cases was undertaken. Further review was then completed after implementation of two improvements—a short notice surgical waiting list and fast track pre-assessment clinics. The results showed that implementation of the reserve surgical waiting list reduced unused operating time by an average of 2.25 hours per month. By further adding in the fast track preassessment clinic, these figures increased to an average of 11.5 hours over the next 3 months. This precipitated a reutilisation of otherwise wasted theatre time. Economic impact of this time amounts around £28 750 a month, after implementation of both improvements. Simple protocol changes can lead to large improvements in the efficient running of theatres. The resultant change has improved patient satisfaction, led to greater training opportunities and improved theatre efficiency. Extrapolation of our results show better usage of previously underused theatre time, to the equivalent worth of £345 000. Further implementation of these improvements in other surgical specialities and hospitals would be beneficial.